Distribution and Identification of Root-knot Nematodes from Turkey - Devran, Zübeyir (The Society of Nematologists, 2009)
Root knot nematodes are causing serious losses in protected cultivation fields in the West Mediterranean region of Turkey. Correct and confident identification of the plant parasitic nematodes is important for vegetable growing and breeding. Therefore, ninety-five populations of plant parasitic nematodes were collected from regional greenhouses. Previously described species-specific primers were used to identify Meloidogyne populations. The present study indicated that SEC-1F/SEC-1R and INCK14F-INCK14R primers for identifying of M. incognita, Fjav/Rjav and DJF/DJR primers for M. javanica and Far/Rar for M. arenaria primers can be effective tools to identify the Turkish root-knot nematode species. Dissemination ratios of the population were 64.2%, 28.4% and 7.3% for Meloidogyne incognita, M. javanica and M. arenaria, respectively. The results showed that M. incognita was the prominent root-knot nematode species in the West Mediterranean coastal areas of Turkey.